Conventional vs. microwave- or mechanically-assisted synthesis of dihomooxacalix[4]arene phthalimides: NMR, X-ray and photophysical analysis - Santos Miranda, Alexandre (2021)
Direct O-alkylation of p-tert-butyldihomooxacalix[4]arene (1) with N-(bromopropyl)- or N-(bromoethyl)phthalimides and K2CO3 in acetonitrile was conducted under conventional heating (reflux) and using microwave irradiation and ball milling methodologies. The reactions afforded mono- and mainly distal di-substituted derivatives in the cone conformation, in a total of eight compounds. They were isolated by column chromatography, and their conformations and the substitution patterns were established by NMR spectroscopy (H-1, C-13, COSY and NOESY experiments). The X-ray structures of four dihomooxacalix[4]arene phthalimide derivatives (2a, 3a, 3b and 5a) are reported, as well as their photophysical properties. The microwave (MW)-assisted alkylations drastically reduced the reaction times (from days to less than 45 min) and produced higher yields of both 1,3-di-substituted phthalimides (3a and 6a) with higher selectivity. Ball milling did not reveal to be a good method for this kind of reaction.